2019
DOI: 10.1097/meg.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of hepatitis B and C viruses among haemodialysis patients: a multicentric study

Abstract: The high prevalence of hepatitis viruses among HD patients of northern Pakistan indicates a close relation between HD centres and hepatitis virus transmission. Therefore, preventive control measures are essential to reduce hepatitis transmission in HD centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…However, it has been noted that the risk of HBV infection correlates with the sex for example grater were recorded in male with 8.6% in male and 5% in female. In the current study, the frequency of HBV in HD patients from Peshawar is similar to the study reported by [15] with 7.5% from ve HD centers in the Hazara division of Pakistan. Thus, the HD does not increase but signi cantly increase hepatitis C infection rates only [25].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, it has been noted that the risk of HBV infection correlates with the sex for example grater were recorded in male with 8.6% in male and 5% in female. In the current study, the frequency of HBV in HD patients from Peshawar is similar to the study reported by [15] with 7.5% from ve HD centers in the Hazara division of Pakistan. Thus, the HD does not increase but signi cantly increase hepatitis C infection rates only [25].…”
Section: Discussionsupporting
confidence: 90%
“…[21] While the study from India conducted by [22] from 1992 to 2000 reported the frequency of HCV in HD was 30% thus HCV among dialysis patients varies markedly from country to country and among dialysis centers within a single country [23]. However, the ratio of HCV is higher in either sex, male or female is not yet clearly understood but we recorded 21% in male and only 20% in female and a similar trend had recorded by [15] with 20.57% in male and 18.18% only in female from Hazara division, Pakistan. While this show contrast with [24] recorded which indicated the ratio of HCV in HD was higher in female as compared to male with 62.50% and 40.13% respectively.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…For example, a prospective, observational study of adult haemodialysis patients randomly selected from 308 dialysis facilities in Europe and the United States during 1988‐2001 demonstrated that the mean HCV prevalence rate was 13.5% and varied from 2.6% to 22.9% between countries . Multiple other studies from various parts of the world reported HCV prevalence between 4% and 40% among patients receiving HD . Given that, even though the prevalence of HCV on HD among Medicare population was substantially higher than in no HD, we believe that our estimate of 4.2% is lower than the true disease burden.…”
Section: Discussionmentioning
confidence: 62%